Reforming the Financial Incentives of the Welfare System - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2000)
This paper summarizes the findings from the Self Sufficiency Project: a large scale social experiment that is being conducted in Canada to evaluate the effect of high-powered financial incentives for full time work among former welfare recipients. The experimental results confirm the importance of financial incentives in the welfare participation and work decisions of lowincome single mothers. Enhanced incentives induce a significant fraction of welfare recipients to leave the program and enter work. They also have a relatively large anti-poverty effect. Moreover, when incentives are offered to relatively short-term recipients, they can actually save the government money.
Keywords: I38; 330; Welfare reform; financial incentives; Workfare; Sozialreform; Selbsthilfe; Ökonomischer Anreiz; Sozialhilfeempfänger; Arbeitsangebot; Kanada